Severe historical floods on the river Roda, Thuringia: from reconstruction to implications for flood management - Deutsch, Mathias; Reeh, Tobias; Karthe, Daniel (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
Using the Roda river (Thuringia) as an example, we present methods for and results of historical flood research in Germany. The Roda river is one of the tributaries of the Saale river with a length of approximately 33 km. Although the watershed only covers around 262 km², the Roda is very vulnerable to flooding. The river caused damages of catastrophic dimensions within the urban area of Stadtroda (until 1925 “Roda”). These damages were especially devastating after heavy rainfall events during the late spring and early summer seasons of June 1582, April 1654, June 1827, June 1871 and June 1876. This article discusses how the flood history of the Roda river and human response to the associated natural hazards can be analysed by a combination of archive and field work. By means of the available material (e.g. printed, handwritten and physical sources as well as maps, engravings and historical photos), the history of severe floods was reconstructed for several centuries. This specifically refers to 1) the genesis, magnitude, frequency and length of floods, 2) the extent of damages and losses, 3) the risk perception and evaluation by municipal and national administrations and 4) the planning and implementation of protective measures and their impacts. Interestingly, the analysis of the disastrous floods of 1871 and 1876 shows striking similarities to the current discussion (e.g. regarding the influence of land use changes). Furthermore, the combined historical accounts are an important basis for the derivation of future flood risk assessments for the Roda river. Going beyond the specific basin of the Roda, the findings also reveal important insights regarding the impacts of increases in heavy regionalized rainfall for small watersheds, which is predicted to occur more frequently in such watersheds in the state of Thuringia.